2022
DOI: 10.1371/journal.pone.0270790
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study of arthropod and onychophoran Fox gene expression patterns

Abstract: Fox genes represent an evolutionary old class of transcription factor encoding genes that evolved in the last common ancestor of fungi and animals. They represent key-components of multiple gene regulatory networks (GRNs) that are essential for embryonic development. Most of our knowledge about the function of Fox genes comes from vertebrate research, and for arthropods the only comprehensive gene expression analysis is that of the fly Drosophila melanogaster. For other arthropods, only selected Fox genes have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 196 publications
0
5
0
Order By: Relevance
“…In S. cephaloptera hatchlings, foxA-expression is also observed in various parts of the digestive tract, particularly in cells lining the foregut, corroborating its conserved regulatory functions during bilaterian digestive tract formation and regionalization [81]. Moreover, Sce-foxA-expression is also detected in the developing brain and the VNC, which resembles the condition in annelids [67][68][69] and ecdysozoans [74,82,83]. While some annelids probably express foxA in the ventral neuroectoderm, foxA is expressed in the floor plate of the developing neural tube of chordates [80,[84][85][86][87].…”
Section: Conserved Expression Of Foxa In the Cns And The Developing F...mentioning
confidence: 73%
See 1 more Smart Citation
“…In S. cephaloptera hatchlings, foxA-expression is also observed in various parts of the digestive tract, particularly in cells lining the foregut, corroborating its conserved regulatory functions during bilaterian digestive tract formation and regionalization [81]. Moreover, Sce-foxA-expression is also detected in the developing brain and the VNC, which resembles the condition in annelids [67][68][69] and ecdysozoans [74,82,83]. While some annelids probably express foxA in the ventral neuroectoderm, foxA is expressed in the floor plate of the developing neural tube of chordates [80,[84][85][86][87].…”
Section: Conserved Expression Of Foxa In the Cns And The Developing F...mentioning
confidence: 73%
“…FoxA is expressed in the foregut of the mollusks Patella vulgata [65] and Crepidula fornicata [66], in the ectodermal foregut and hindgut of annelids [67][68][69][70] and the planarians Dugesia japonica [71] and Schmidtea polychroa [72]. In addition, expression of foxA in the pharynx has also been reported for Phoronida [73], Ecdysozoa [74][75][76][77], and Chordata [78][79][80]. In S. cephaloptera hatchlings, foxA-expression is also observed in various parts of the digestive tract, particularly in cells lining the foregut, corroborating its conserved regulatory functions during bilaterian digestive tract formation and regionalization [81].…”
Section: Conserved Expression Of Foxa In the Cns And The Developing F...mentioning
confidence: 89%
“…[ 78 , 146 ]. A recent study has shown that in Parasteatoda , FoxF1 is almost exclusively expressed in the visceral mesoderm of the opisthosoma [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…The only previously investigated spider genes that represent markers of Cluster-XXII are the two forkhead domain transcription factors FoxC / crocodile ( croc ) (LOC107456536) and FoxA / forkhead ( fkh ) (LOC107452746), six3 (LOC107450741), and visual system homeobox ( vsx ) (LOC122268388). In Parasteatoda and other spiders, these genes are expressed in the stomodaeum and along the split ventral midline [ 84 , 89 , 111 , 163 ]. Expression of unc5848 , unc3843 , and anapece , however, shows that these top markers are expressed exclusively in the stomodaeum, or strongly in the stomodaeum and faintly at the edges of the split ventral midline (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation